TINGKAT KEPUASAN PENGUNJUNG OBJEK WISATA D’MOOAT DI DESA MOOAT KECAMATAN MOOAT KEBUPATEN BOLAANG MONGONDOW TIMUR - Meygi Anggi Sayekti Ratu; Benny Adrian Berthy Sagay; Elsje Pauline Manginsela (AGRI-SOSIOEKONOMI, 2018)
This study aims to determine the level of satisfaction of tourist visitors. This research was conducted for 3 months from May to July 2018 in D’Mooat Tourism Object, in Mooat Village, Mooat Subdistrict, East Bolaang Mongondow Regency. The method used in this study is direct interviews with visitors based on a questionnaire. The number of respondents is 30 people. The method of data analysis used an attitude measurement scale or a Likert Scale. The results showed that the index number of visitors' satisfaction at D’Mooat attractions was at the point of 72.44% which was classified as the level of "Satisfaction".*eprm*.